BIOMETRIC ANALYSIS AND BREAKING OF DORMANCY OF SEEDS OF Piptadenia viridiflora (Kunth) Benth - Vieira Cangussu, Anne Caroline; Caetano, Ana Paula Oliveira; Santos, Jerffson Lucas; Castro Filho, Manoel Nelson de; Cardoso, Adriana Dias (Floresta, 2018)
The objective of this study is to evaluate the biometric characteristics and the efficiency of treatments using mechanical scarification and immersion in water at different temperatures to break the dormancy of seeds of surucucu [Piptadenia viridiflora (Kunth) Benth], a tree with several uses and adapted to the semiarid conditions of the northeast of Brazil. The biometric analysis of the seeds was conducted using a digital caliper. The mean length, width, and thickness of 100 seeds were measured. The study adopted a completely randomized experimental design, with six treatments and four repetitions of 25 seeds per plot, totaling 100 seeds per treatment. The experiment consisted of control treatment (seeds without scarification), treatment with mechanical scarification on sandpaper, and heat treatment at 60, 70, 80 and 90 ºC for 5 min. The average size of the seeds was 8.050 mm in length, 6.529 mm in width, and 0.997 mm in thickness. For breaking dormancy, scarification on sandpaper and water immersion at 70 °C produced higher percentages of germination and emerged seedlings.